New Insights into Circular Economy and Sustainable Development - Koval, Viktor; Atstaja, Dzintra; Skačkauskienė, Ilona (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is devoted to fundamental and applied research in the field of implementing the principles of the circular economy in energy transition, and it substantiates the need for its transformation in the context of sustainable development. Of particular interest are promising areas for the use of secondary energy resources in the economy to create closed production cycles. Specific technologies are considered, and their environmental and economic assessments of scenarios for the introduction of low-carbon technologies in the circular economy, the achievement of the Sustainable Development Goals through the introduction of a circular economy, and the development of regional cooperation are given. Particular attention is paid to the possibility of using eco-innovations for the national transition to decarbonization in the integrated European energy system, Green intellectual capital as a support for corporate environmental development, a sustainable value chain for the industrial consumption of biocomposites, and various options for programs to reduce CO2 emissions.